Multi-channel deployment: a methodology for the design of multi-channel service processes - Sousa, Rui (2016)
This study develops a methodology for assisting service providers in the choice of the service channels (e.g. physical facilities, the Internet, phone) to employ to support the delivery to customers of the several stages of a service process (from information search to after-sales). We build on the principles of the service concept, service blueprinting and quality function deployment (QFD) to develop a stepwise procedure for: (i) translating customer requirements into a corresponding service concept across distinct service process stages; and (ii) specify the channels that support customer interaction at each stage. Based on the QFD logic, the multi-channel deployment methodology employs a number of matrices that consider the way channel choices fit with the intended service concept, considering both the customer and the provider perspectives, thus aligning ‘the voice of the customer’ with the ‘voice of the provider’.